A Co(II) coordination complex: local analgesia activity by reducing content of local acetylcholine. Issue 10 (10th August 2020) - Xie, Shuang; Li, Xuan-Fa; Xiu, Zhi-Xin; Chen, Jianhui
Abstract: A new Co(II)-containing coordination complex with the chemical formula of [CoL2 (SCN)2 ](H2 O)2 (1 ) has been assembled from the Co(NO3 )2 ·6H2 O with a tripyridyltriazole ligand 3-(2-pyridyl)-4-(4-pyridyl)-5-(3-pyridyl)-1, 2, 4-triazole by introduction of the NH4 SCN as the additive reagent. Complex 1 has been studied via the single-crystal X-ray diffraction, elemental analysis, powder X-ray diffraction (PXRD) along with the thermogravimetric (TG) analysis. Furthermore, its local anesthesia activity was evaluated. Firstly, the hot plate analgesic experiment was performed, and the local anesthesia activity was assessed. In addition to this, the levels of the acetylcholine in local were also measured with ELISA detection kit. Graphical Abstract: UF0001 A new Co(II)-containing coordination complex has been assembled from the Co(NO3 )2 ·6H2 O with a tripyridyltriazole ligand 3-(2-pyridyl)-4-(4-pyridyl)-5-(3-pyridyl)-1, 2, 4-triazole by introduction of the NH4 SCN as the additive reagent. The local anesthesia activity of 1 was evaluated via hot plate analgesic experiment. The ELISA study was performed to measure the content of acetylcholine in local.